Application Of Dryer Machines In The Development Of Karo Traditional Herb Business In Tambar Malem Group In Batu Jong Jong Village, Langkat, North Sumatra - Yayuk Yuliana; Yayuk Putri Rahayu; Harianto II; Cici Niken Ariyanti; Ghalih Anwar (International Journal Of Community Service, 2022)
The partner of the service activity is the Tambar Malem Group which is engaged in the business of Karo traditional herbs for traditional medicinal ingredients. The Tambar Malem group which consists of housewives to date still producing traditional Karo ingredients . Mitra is located in Bahorok District, Langkat Regency, North Sumatra Province. Partner problems in the field of production. In production still use simple tools and manuals so the amount of production is still small. The implementation method uses education and counseling,focus group discussions, ,accompaniment, evaluation. Solutions to partner priority problems from (1) Aspectproduction including Focus Group Discussion (2) procurement and use of equipment (3) preparation of materials; (3) Implementation of training (4) Evaluation. The results of the service activities Increasing knowledge and management skills of business development and implementation of drying machine technology